The FlimFlam affair - Pronzini, Bill (Muller, Marcia. Carpenter and Quincannon mystery., 2019)
Carpenter and Quincannon Professional Detective Services is a fixture in San Francisco at the dawn of a new century. Sabina and John will protect their clients, doing what is necessary to run the dregs of society into the arms of the law. Sometimes that involves brute force. Other times, a more subtle touch is needed. Professor A. Vargas, medium extraordinaire, and his partner, Annabelle, don't use picks to open locked doors, and most certainly don't use violence to get what they want. Instead they prey upon hopes and fears to swindle bereaved patrons. Soon John and Sabina find themselves in a dusky room, preparing to take the lying duo down. Then a knife flashes ... and our detectives must discover who is conning whom. Before they themselves are dispatched.